Jorge de Sena’s camonian tetralogy - Laurentino, Lucas (2025)
The objective of this article is to provide a comprehensive overview of the principal works authored by Jorge de Sena concerning Camões. It seeks to illustrate that these studies, rather than being a mere collection of essays, represent integral components of a broader project aimed both at a general re-interpretation of Camões’ poetry and at the formulation of a critical methodology to be employed in literary and cultural studies.